Additive manufacturing: a new design approach-LPBF design and production flow chart algorithm - Çalışkan, Cemal İrfan; Arpacıoğlu, Ümit (Progress in additive manufacturing, 2025)
With additive manufacturing (AM) technologies completely changing the traditional design and manufacturing processes, there is a need for reinterpretation and redefinition of many design methods and constants that have been applied within the scope of the production system and the material used, and new process and design strategies are needed. In this context, in this study, an algorithm has been developed for the laser powder bed fusion (LPBF) system, an industrial metal AM technology, in which the process and its stages are defined. In the algorithm, the stages from the formation of the design idea to the finalization of the production are discussed. The designer and engineer who wants to develop a product to be produced in the LPBF production system can be produced by following the relevant stages through the algorithmic model, and product development is supported without the need for multiple revision stages. With the algorithm, it is aimed to define the approach of AM-LPBF technology that challenges the traditional design theory and methodology within the scope of certain criteria brought by the technology and to systematize the process data. It can be stated that this process modeling and algorithm developed in the field of AM offers innovation within the scope of preventing inefficient revision processes, quality production and fast solution generation. Within the scope of the developed algorithm, it is aimed at the experts in the field to complete the design and production processes that fit the production system with fewer revision stages without compromising product quality.